Efektivitas Model Peningkatan Kompetensi Profesional Guru Biologi Berbasis Continuous Professional Development (CPD) di Karesidenan Surakarta - Anif, Sofyan; Zain, Almuntaqo (Jurnal Varidika: Varia Pendidikan, 2015)
TheÂ  IndonesianÂ  LawÂ  No.Â  14Â  YearÂ  2005Â  onÂ  teacherÂ  andÂ  lecturerÂ  and Government Regulation No 74 Year 2008 on teacher, have mandated the government to carry out certiï¬ cation for teachers of all subjects who have met the requirements. Based on a survey conducted by the Directorate General of Quality Improvement of Teachers and Education PersonnelÂ  (PMPTK) in 2009, the certiï¬ cation program has not been able to improve the competence and professionalism of teachers signiï¬ cantly so it has not given positive inï¬ uence on improving the performance of teachers. The purpose of this study is to determine the effectiveness of the model of professional competenceÂ  improvementÂ  ofÂ  biologyÂ  teacherÂ  basedÂ  onÂ  initialÂ  competenceÂ  testÂ  in Surakarta.This research uses R & D approach developed by Borg and Gall (2007), which includes six procedures or stages of development: (1) determine the product; (2) conduct a theoretical and empirical study; (3) development planning; (4) the development of early models; (5) validation of the model; and (6) the discovery of the ï¬ nal product. The ï¬ rst up to the fourth stage has been done in previous studies, and this research isÂ  theÂ  ï¬ fthÂ  stageÂ  namelyÂ  theÂ  stageÂ  ofÂ  modelÂ  validationÂ  throughÂ  limitedÂ  experiment withÂ  one-groupÂ  pretest-PosttestÂ  Design.Â  WhileÂ  theÂ  dataÂ  analysisÂ  usesÂ  traditional descriptive quantitative approach.The results of the study on the effectiveness of implementation of the model of increasing BiologyÂ  teacherÂ  competenceÂ  basedÂ  onÂ  CPDÂ  on Â aÂ  limitedÂ  scaleÂ  testÂ  showÂ  thatÂ  the classical absorption of pretest is 27.78%, while the classical absorption of post-test is 72.22%. It means that Biology teacher competence based on CPD has increased in a limited test scale of 44.44%. The results of a statistical analysis of the increase of pre- test and post-test absorption on each competence shows that the greatest increase of percentage in absorption was on the competence: âunderstanding the concepts, laws, and theories of biology and ï¬ exible implementationâ for 38.89%. While the lowest increase of percentage in the absorption occurred on the competence: âconducting action research to increase professionalismâ with only 13.27%.